Russia - Thayer, Charles W. (Charles Wheeler), 1910-1969. (New York : Time, inc., 1965)
A description of the land and people of Russian, stressing the government and its influence of the social life, education, and culture of Soviet citizens.
Bibliography: p. 170-171.
Keywords: Soviet Union